Manusia dan Kebebasan dalam Fenomena Childfree Ditinjau dari Perspektif Filsafat Eksistensialisme Jean-Paul Sartre - Siswadi, Gede Agus; Cahyana, Abdul Basit (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2024)
This research explores the phenomenon of childfree in the light of Jean-Paul Sartre’s philosophy of existentialism. In Sartre’s view, the absolute freedom of the individual is at the core of human existence, and the decision not to have children can be interpreted as the most fundamental expression of individual freedom. This research aims to investigate how the concepts of freedom and responsibility in Sartre’s existentialism shape human understanding of the childfree phenomenon. The method used in this research is a qualitative method with a philosophical hermeneutic approach. The data in this study were obtained through library research and also critical reflection. The results showed that the childfree decision is a real manifestation of individual freedom in shaping the meaning of life. The childfree decision can also be based on the understanding that happiness or life fulfilment does not always depend on the role of parenthood. The concept of responsibility, as described by Sartre, plays an important role in making such decisions. As an individual or childfree couple can freely determine priorities and life values that suit their desires. This research is expected to provide additional insights related to childfree life choices and contribute to the understanding of existentialism philosophy in the context of human life decisions.